2016
DOI: 10.3319/tao.2016.02.07.01(hy)
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo Forest Water Use Efficiency in the Yangtze River Delta Region, China

Abstract: An eddy covariance technique was used to measure the gross primary productivity (GPP), evapotranspiration (ET), and water use efficiency (WUE) during the 2011 -2014 period over a moso bamboo forest at a site in Anji (AJ), China. WUE declined during the severe summer drought of 2013 when the vapor pressure deficit (VPD) was above 15 hPa, and was significantly higher than the average value. At AJ the average annual GPP, ET, and WUE were 1522 ± 73 C m -2 year -1 , 693 ± 41 kg H 2 O m -2 year -1 , and 2.21 ± 0.23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…Their results showed that NPP in terrestrial ecosystems in the YRD region also showed a decreasing trend. This was mainly caused by global climate change, the frequency of summer droughts has increased in this region, and severe summer droughts have led to a decline in vegetation productivity (Zhao and Running 2010;Wang et al 2016). Along with freezing rain and ice storms, GPP in the YRD region has gradually shown a decreasing trend (Xu et al 2013).…”
Section: Temporal and Spatial Variations Of Gppmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that NPP in terrestrial ecosystems in the YRD region also showed a decreasing trend. This was mainly caused by global climate change, the frequency of summer droughts has increased in this region, and severe summer droughts have led to a decline in vegetation productivity (Zhao and Running 2010;Wang et al 2016). Along with freezing rain and ice storms, GPP in the YRD region has gradually shown a decreasing trend (Xu et al 2013).…”
Section: Temporal and Spatial Variations Of Gppmentioning
confidence: 99%
“…Therefore, to use the rare and precious water resources efficiently and reasonably, it is essential to understanding the characteristics of GPP, ET, WUE, and their relationship with related driving factors. Meanwhile, understanding the GPP, ET, WUE characteristics, and their relationship with related factors can greatly enhance our knowledge of their control processes as well as the adaptation mechanism of carbon and water cycle to climate change (Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…中消耗水形成有机物质的基本效率, 是确定植物体 生长发育所需最优水分供应的重要指标 (Bohn & Kershner, 2002), 它也在一定程度上反映了植物的 耗水性和干旱适应性 (Munns, 2005) (孙学凯等, 2008), 也是植物适应 干旱环境的一种重要生理指标 (Jaleel et al, 2008)。 研究WUE的时间变化特征及其与外界驱动因子之 间的关系不仅有助于增进对生态系统水碳循环过程 与驱动机制的理解 (Wang et al, 2016), 而且对模拟 和评估生态系统对未来气候变化的响应具有重要意 义 (Guo et al, 2010) (Beer et al, 2009;李辉东等, 2015;Wang et al, 2016;Liu et al, 2017)。但上述研究大多是集中在单 一时间尺度下开展的分析。已有研究发现, 在不同 时间尺度下WUE呈现不同的时间变化特征 (Song et al, 2017), 控制生态系统WUE的主导因子也会随着时 间尺度的变化而变化。比如多数研究发现饱和水汽 压差(VPD)与WUE呈负相关关系, 但这种关系多局 限于短时间尺度的研究 (Ponton et al, 2006;胡中民 等 , 2009), 也有研究发现随着时间尺度的扩大, VPD与WUE并无明显关系 (Liu et al, 2017;Song et al, 2017) (Tang et al, 2015):…”
Section: 植物的水分利用效率(Wue)是其生理活动过程unclassified